Carbon footprint comparison of video intubation tools: Disposable laryngoscopes, reusable laryngoscopes, and stylets - Danyang Pan; Yating Yang; Sirui Chen; Jinhe Deng; Gaofeng Zhao; Min Zhong (PLoS ONE, 2025)
Purpose As healthcare systems grapple with their 5% global carbon footprint contribution, sustainable medical device selection emerges as a critical decarbonization lever. This life cycle assessment (LCA) quantifies environmental disparities among three prevalent video intubation tools—Disposable video laryngoscopes (VLs), reusable VLs, and video Stylets—to guide evidence-based procurement. Methods Using International Organization for Standardization (ISO)14040 compliant life cycle assessment (LCA) methodology—the international standard defining LCA principles and framework—we quantified cradle-to-grave emissions for three video intubation devices manufactured by Zhejiang UE Medical Corp. The functional unit (one tracheal intubation) incorporated material extraction, manufacturing, low-temperature LTPS/ HLD, transportation, and disposal. SimaPro 9.4.0 with Ecoinvent 3.8 database calculated CO₂ equivalents (kg CO₂e), validated through sensitivity analyses of sterilization loading (10–80 devices/cycle) and regional grids. Results The HLD-disinfected video stylet demonstrated superior environmental performance, emitting 98.24 kg CO₂e per 500 procedures—45.8% and 42.0% lower than reusable VLs (181.45 kg CO₂e) and disposable VLs (169.47 kg CO₂e), respectively. Sensitivity analyses identified sterilization loading as the dominant variable: half-load (50% chamber utilization) reduced emissions by 89–91% versus single-device processing, with full-load optimization yielding incremental 11–14% reductions. Process and regional variability further revealed that HLD decreased emissions by 19–24% compared to LTPS, while grid carbon intensity caused 24–33% variability (India vs. EU). Scenario comparisons confirmed the video stylet’s environmental dominance across sterilization methods—even with LTPS (349.99 kg CO₂e/500 uses), it maintained a 45% reduction over reusable VL baselines, whereas HLD-treated video stylets (94.32 kg CO₂e) showed 6.7-fold lower emissions than disposable VLs and 59% below HLD-reprocessed reusable VLs. Conclusions HLD-reprocessed video stylets are the environmentally optimal choice for high-volume, low-infection-risk settings. For low-throughput or high-risk scenarios, providers should balance environmental impacts with clinical requirements through frequency and resource assessment.